Utility of the Microculture Method in Non-Invasive Samples Obtained from an Experimental Murine Model with Asymptomatic Leishmaniasis - Allahverdiyev, Adil M.; Bagirova, Malahat; Cakir-Koc, Rabia; Elcicek, Serhat; Oztel, Olga Nehir; Canim-Ates, Sezen; Yesilkir-Baydar, Serap (Amer Soc Trop Med & Hygiene, 2012)
The sensitivity of diagnostic methods for visceral leishmaniasis (VL) decreases because of the low number of parasites and antibody amounts in asymptomatic healthy donors who are not suitable for invasive sample acquisition procedures. Therefore, new studies are urgently needed to improve the sensitivity and specificity of the diagnostic approaches in non-invasive samples. In this study, the sensitivity of the microculture method (MCM) was compared with polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA), and immunofluorescent antibody test (IFAT) methods in an experimental murine model with asymptomatic leishmaniasis. Results showed that the percent of positive samples in ELISA, IFAT, and peripheral blood (PB) -PCR tests were 17.64%, 8.82%, and 5.88%, respectively, whereas 100% positive results were obtained with MCM and MCM-PCR methods. Thus, this study, for the first time, showed that MCM is more sensitive, specific, and economic than other methods, and the sensitivity of PCR that was performed to samples obtained from MCM was higher than sensitivity of the PCR method sampled by PB.
Keywords: Polymerase-Chain-Reaction; Visceral Leishmaniasis; Endemic Area; Canine Leishmaniasis; Peripheral-Blood; Western-Blot; in-Vitro; Diagnosis; Infection; Dogs